Multicomponent Synthesis of 2-(2,4-Diamino-3-cyano-5H-chromeno[2,3-b]pyridin-5-yl)malonic Acids in DMSO - Yuliya E. Ryzhkova (MDPI AG, 2021)
Dimethyl sulfoxide is a widely used solvent in organic synthesis and in the pharmaceutical industry because of its low cost, stability, and low toxicity. Multicomponent reactions are an advanced approach that has become an efficient, economical, and eco-friendly substitute for the conventional sequential multi-step synthesis of various biologically active compounds. This approach was adopted for the synthesis of previously unknown 2-(2,4-diamino-3-cyano-5H-chromeno[2,3-b]pyridin-5-yl)malonic acids via transformation of salicylaldehydes, malononitrile dimer, and malonic acid. It was shown that the use of DMSO at room temperature makes it possible to synthesize previously unavailable compounds. The investigation of the reaction mechanism using 1H-NMR monitoring made it possible to confirm the proposed mechanism of the transformation. The structure of synthesized 5H-chromeno[2,3-b]pyridines was confirmed by 2D-NMR spectroscopy.